Mutational and transcriptomic landscapes of a rare human prostate basal cell carcinoma. Issue 6 (2nd March 2020) - Su, Xianbin; Long, Qi; Bo, Juanjie; Shi, Yi; Zhao, Li‐Nan; Lin, Yingxin; Luo, Qing; Ghazanfar, Shila; Zhang, Chao; Liu, Qiang; Wang, Lan; He, Kunyan; et al.
Abstract: Background: As a rare subtype of prostate carcinoma, basal cell carcinoma (BCC) has not been studied extensively and thus lacks systematic molecular characterization. Methods: Here, we applied single‐cell genomic amplification and RNA‐Seq to a specimen of human prostate BCC (CK34βE12 + /P63 + /PAP − /PSA − ). The mutational landscape was obtained via whole exome sequencing of the amplification mixture of 49 single cells, and the transcriptomes of 69 single cells were also obtained. Results: The five putative driver genes mutated in BCC are CASC5, NUTM1, PTPRC, KMT2C, and TBX3, and the top three nucleotide substitutions are C>T, T>C, and C>A, similar to common prostate cancer. The distribution of the variant allele frequency values indicated that these single cells are from the same tumor clone. The 69 single cells were clustered into tumor, stromal, and immune cells based on their global transcriptomic profiles. The tumor cells specifically express basal cell markers like KRT5, KRT14, and KRT23 and epithelial markers EPCAM, CDH1, and CD24 . The transcription factor covariance network analysis showed that the BCC tumor cells have distinct regulatory networks. By comparison with current prostate cancer datasets, we found that some of the bulk samples exhibit basal cell signatures. Interestingly, at single‐cell resolution the gene expression patterns of prostate BCC tumor cells show uniqueness compared with that of common prostate cancer‐derived circulating tumor cells. Conclusions: This study, for the first time, discloses the comprehensive mutational and transcriptomic landscapes of prostate BCC, which lays a foundation for the understanding of its tumorigenesis mechanism and provides new insights into prostate cancers in general.